Examining How Preschool Teachers’ Positive Psychological Capital Impacts Digital Education Innovation: A Moderated Moderation Analysis of Effort Expectancy and Behavioral Intention - Myoung-Sun Sung; Young-Eun Lee (Behavioral Sciences)
This study examines the impact of preschool teachers’ positive psychological capital on their digital education innovation behavior, focusing on the moderated moderation effects of digital education effort expectancy and behavioral intention on this relationship. Data were analyzed from 211 preschool teachers of children aged 3–5 years in South Korea. SPSS (version 25.0) was used to conduct descriptive and Pearson correlation analyses, and PROCESS Macro (version 4.3) was used to perform the moderation analysis. The results indicate that preschool teachers with higher positive psychological capital exhibited increased innovation behavior toward digital education, and this effect was further strengthened by higher effort expectancy. These research findings can provide useful foundational data for designing teacher training programs to promote preschool teachers’ digital education innovation behavior.